Penerapan Media Pembelajaran Berbasis Quizziz dalam Meningkatkan Hasil Belajar Siswa pada Mata Pelajaran Informatika Kelas X di SMA Negeri 5 Maros - fitrah wahyuni; Muhammad Rizki Akbar; Nasir Nasir (Institut Nalanda, 2024)
This research is classroom action research which aims to determine the improvement in student learning outcomes in the class X informatics subject at SMA Negeri 5 Maros. The subjects of this research were class X of SMA Negeri 5 Maros for the 2023/2024 academic year with a total of 35 people. This research was carried out in two cycles and each cycle consisted of 6 meetings. The results of this research show that the application of Quizziz-based learning media can improve the effectiveness and learning outcomes of students in informatics subjects. Quantitative analysis shows that learning outcomes in the initial test were 38.88%, in cycle I there was an increase of 52.77% and then in cycle II it was 100%. This means that there is a significant increase in student learning outcomes.